Inovasi Teknologi Generator Listrik Independen sebagai Sumber Energi Listrik Terbarukan dan Penggunaan Lampu Light Emition Diode (LED) pada Bagan Perahu - Risal Anto Aprianto (Hasanuddin Student Journal, 2018)
ABSTRACT: Canoe bagan is one of the lift net were operated on shore or coastal waters at night by using light as a means of towing the fish. Generally chart in South Sulawesi operated using a generator to provide energy. Operation bagan by using genset or generator sets will increase spending, thereby reducing the effectiveness of the fishing gear. The purpose of this research is to create a source of electrical energy environmental friendly renewable canoe bagan and actually can be adapted into afield capture of light fishing and to boost the productivity and income of fishing communities especially fishing canoe bagan. The research method is the stage design, the machine frame, shaft fly whell, and manufacture a series of LED lights. The results showed independent power generator can’t function as expected because of the electrical energy generated can’t be used to rotate the electro motors as prime movers of independent power generator. Voltage generated by the generator 122 volts necessary to add the inverter so as to produce a voltage 220.